2020
DOI: 10.1186/s12967-020-02399-5
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits and lifestyle changes during COVID-19 lockdown: an Italian survey

Abstract: Background: On December 12th 2019, a new coronavirus (SARS-Cov2) emerged in Wuhan, China, sparking a pandemic of acute respiratory syndrome in humans (COVID-19). On the 24th of April 2020, the number of COVID-19 deaths in the world, according to the COVID-Case Tracker by Johns Hopkins University, was 195,313, and the number of COVID-19 confirmed cases was 2,783,512. The COVID-19 pandemic represents a massive impact on human health, causing sudden lifestyle changes, through social distancing and isolation at ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

248
1,864
46
147

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,759 publications
(2,305 citation statements)
references
References 40 publications
248
1,864
46
147
Order By: Relevance
“…Nevertheless, such action may exert a sudden and drastic change in the lifestyle of the population. It has been reported that staying at home for a long time may lead to a change in dietary habit, physical activity, and sleep patterns, in addition to psychological impact (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, such action may exert a sudden and drastic change in the lifestyle of the population. It has been reported that staying at home for a long time may lead to a change in dietary habit, physical activity, and sleep patterns, in addition to psychological impact (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Home con nement for several months could lead to weight gain, further increasing incidence of obesity (5).To many patients in Italy, weight gain was found related to increased self-reported anxiety or depression and not consuming healthy food in obese adults according to multiple regression analysis (6). In Poland, almost 30% of people gain weight of 3.0 ± 1.6 kg, and it seemed that overweight, obese and older individuals were more likely to gain weight (7). Because of school closures resulting from COVID-19, the risk of weight gain increased for children in USA (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Even if some positive outcomes related to staying at home have been highlighted, such as the adoption of healthier eating habits and the increase of sleep hours 27 , reports show that movement restrictions aimed to stop the spread of the virus are causing a worldwide increase in family problems and domestic violence 28,29 . A systematic review 30 documented that family conflict is the most commonly reported precipitant of suicidal acts among children.…”
mentioning
confidence: 99%